(untitled) (Eurasian Medical Research Periodical, 2022)
Pseudomonas aeruginosa is a gram negative bacterium ,causes many infections specially in immunocompromised individuals and causes critical infections in cystic fibrosis patients. It has remarkable ability to resist various kinds of antibiotics by intrinsic , acquired and adaptive resistance mechanisms , because of the diversity in resistance mechanisms this bacterium contributes in developing multidrug-resistant strains. P.aeruginosa infections’ treatment is considered as a significant challenge which need to develop new therapies to treat these infections